Prospects of energy release and mechanical behavior of reactive high-entropy alloys - Shanghao Wu; Zezhou Li; Jianye He; Fan Zhang; Lin Wang; Lei Zhang; Xingwang Cheng (Defence Technology)
High-entropy alloys (HEAs) with multi-component elements have attracted significant interest since they exhibit numerous superior properties compared to traditional ones. These properties include significant energy release, remarkable fracture toughness, and high strength, making them promising candidates as energetic structural materials (ESMs). This paper summarizes the energy release mechanisms under dynamic impact and the mechanical behavior of TiZr-based HEAs, TiNb-based HEAs, and W-based HEA, including velocity threshold for energy release, chamber quasi-static pressure curve, energy release efficiency, interface reactions, and ''self-sharpening''. In addition, we propose future research directions for their energy release and mechanical behavior.